Implementasi Sistem Informasi Manajemen Di Smp Islam Terpadu Al Ummah Jombang: Implementation of Management Information Systems at Al Ummah Integrated Islamic Junior High School Jombang - Solechan Solechan (Chalim Journal of Teaching and Learning (CJoTL), 2021)
Information is an important thing in any place. No exception in the world of education. In an educational institution, the existence of information can help and bring benefits in many ways, some of which include formulating policies and determining programs that will be launched by schools. The existence of accurate information cannot be separated from a good management system and is supported by qualified human resources in educational institutions. So as to produce professional school governance. This paper will review how the implementation of management information systems in SMP Islam Terpadu al-Ummah Jombang. Data collection techniques through interviews, observation, and documentation. Analysis of the data used through data reduction, data presentation, and conclusion. The results of this research are 1. Application of Management Information Systems at SMP Islam Terpadu al-Ummah Jombang using Dapodik data processing applications and information technology to support the learning process. 2. Factors that support the management information system with the Dapodik system to collect data on educators, students, and employees. The inhibiting factors for the implementation of the Management Information System are errors and delays in providing data from each work unit.